Proof-of-principle demonstration of a pilot bunch comagnetometer in a stored beam - J. Slim; F. Rathmann; A. Andres; V. Hejny; A. Nass; A. Kacharava; P. Lenisa; N. N. Nikolaev; J. Pretz; A. Saleev; V. Shmakova; H. Soltner; et al. (Physical Review Research)
In polarization experiments at storage rings, one of the challenges is to maintain the spin-resonance condition of a radio-frequency spin rotator with the spin precessions of the orbiting particles. Time-dependent variations of the magnetic fields of ring elements lead to unwanted variations of the spin-precession frequency. We report here on a solution to this problem by shielding (or masking) one of the bunches stored in the ring from the high-frequency fields of the spin rotator, so that the masked pilot bunch acts as a comagnetometer for the other signal bunch, tracking fluctuations in the ring on a time scale of about one second. While the new method was developed primarily for searches of electric dipole moments of charged particles, it may have far-reaching implications for future spin physics facilities, such as the EIC and NICA.